Korean Cultural Proximity towards Asian Audiences - Julina Tajul Ariffin; Aisyah Mohd Yasim; Mohamed Izzat Mohamed Khalil; Kenchana Wati Md Yusof (Environment-Behaviour Proceedings Journal, 2025)
This study examines the appeal of Korean dramas among Asian audiences, focusing on Korean cultural proximity’s role in shaping viewer preferences. It explores how themes like family values, love, and perseverance resonate across various Asian countries, including Malaysia. Through qualitative interviews with Korean media participants and Malaysian industry experts, the research reveals how Korean dramas harmonize traditional and modern values, aligning with shared Asian sensibilities. The findings suggest that the success of Korean dramas lies in their ability to evoke familiarity and nostalgia, transcending regional boundaries while maintaining a distinct cultural identity.